Effects of biological therapies on patients with Type-2 high asthma and comorbid obesity - Garg, Diya; Que, Loretta G.; Ingram, Jennifer L. (Frontiers in Pharmacology, 2024)
Over 20 million adults and 6 million children in the United States (US) have asthma, a chronic respiratory disease characterized by airway inflammation, bronchoconstriction, and mucus hypersecretion. Obesity, another highly prevalent disease in the US, is a major risk factor for asthma and a significant cause of diminished asthma control, increased submucosal eosinophilia, and reduced quality of life. A large subgroup of these patients experiences severe symptoms and recurrent exacerbations despite maximal dosage of standard asthma therapies. In the past two decades, the development of biological therapies has revolutionized the field and advanced our understanding of type 2 inflammatory biomarkers. However, patients with obesity and comorbid asthma are not principally considered in clinical trials of biologics. Large landmark cluster analyses of patients with asthma have consistently identified specific asthma phenotypes that associate with obesity but may be differentiated by age of asthma onset and inflammatory cell profiles in sputum. These patterns suggest that biologic processes driving asthma pathology are heterogenous among patients with obesity. The biological mechanisms driving pathology in patients with asthma and comorbid obesity are not well understood and likely multifactorial. Future research needs to be done to elicit the cellular and metabolic functions in the relationship of obesity and asthma to yield the best treatment options for this multiplex condition. In this review, we explore the key features of type 2 inflammation in asthma and discuss the effectiveness, safety profile, and research gaps regarding the currently approved biological therapies in asthma patients with obesity.